Influence of the parental virus strain on the virulence and immunogenicity of recombinant vaccinia viruses expressing HBV preS2-S protein or VZV glycoprotein I - Kutinová, L; Ludvíková, V; Krystofová, J; Otavová, M; Simonová, V; Nĕmecková, S; Hainz, P; Vonka, V (Vaccine, 1996)
Five triple-plaque purified vaccinia virus (VV) lines generated from smallpox Sevac VARIE vaccine (strain Praha) and three VV virus lines similarly derived from Wyeth DRYVAX vaccine were used for preparation of recombinants expressing the hepatitis B virus preS2-S gene. The same five Praha-derived virus lines were used to construct recombinants expressing the varicella-zoster virus (VZV) glycoprotein I (gpI) gene. Recombinants and their parental viruses were tested for the residual neurovirulence in mice. The virus lines and the recombinants derived therefrom differed markedly in this respect. Immunization of mice resulted in high levels of anti-HBsAg antibodies only in the case of recombinants derived from the relatively virulent viruses. In contrast, the levels of VZVgpI antibodies in mice were similar with all VV-VZV recombinants irrespective of the virulence of the parental virus line.
Keywords: Mice, Inbred ICR; Cell Line; Hepatitis B Surface Antigens; Vaccinia virus; Herpesvirus 3, Human; virulence; Antibodies, Viral; Mice; genetické vektory; proteinové prekurzory; proteiny virového obalu; hepatitida B - antigeny povrchové; Protein Precursors; virus varicella zoster; ženské pohlaví; Genetic Vectors; zvířata; Virulence; myši inbrední ICR; Species Specificity; protilátky virové; myši; Viral Envelope Proteins; buněčné linie; druhová specificita; syntetické vakcíny; Female; virus vakcinie; Vaccines, Synthetic; Animals